(untitled) (REMUNOM, 2025)
Chromatic mutations in vertebrates have a low frequency of occurrence, despite affecting a large number of species. Furthermore, leucism is confused with albinism, while leucism is defined as the partial or total loss of melanin, the result of genetic mutations with great variations in inheritance mechanisms and associated genes. In September 2021, at around 7 am, we recorded an adult female Mesoclemmys raniceps, sunbathing on a dam embankment in a rural area of Juara-MT. In addition to being the first record of leucism for the species, this record increases the species’ distribution by 100km south of the nearest record.